Methane oxidation catalyst for improving sulfur tolerance and regeneration capacity, preparation method and application thereof

By adding ZrO2, CeO2 or TiO2 as catalyst aids to the alumina-supported Pd catalyst, the problem of reduced activity and difficulty in regeneration of the catalyst in the presence of sulfur is solved, and the sulfur resistance and regeneration ability of the catalyst are significantly improved. It is suitable for exhaust purification systems of lean-burning natural gas engines.

CN119633808APending Publication Date: 2025-03-18THE UNIV OF NOTTINGHAM NINGBO CHINA +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411571215.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing methane oxidation catalysts have reduced activity and are difficult to regenerate in the presence of sulfur, especially in the exhaust gases of lean-burning natural gas engines, and the catalysts have insufficient sulfur resistance and regeneration capabilities.

Method used

By adding ZrO2, CeO2 or TiO2 to the alumina-supported Pd catalyst as a catalyst additive, the low-temperature decomposition of sulfur is promoted, and the sulfur resistance and regeneration ability of the catalyst are improved.

Benefits of technology

It significantly improves the sulfur resistance and regeneration ability of the catalyst, effectively decomposes the surface sulfate under drying reaction conditions, completely restores the activity of the poisoned catalyst, and is suitable for the exhaust of water-containing sulfur-containing lean natural gas vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633808A_ABST
    Figure CN119633808A_ABST
Patent Text Reader

Abstract

The invention relates to a methane oxidation catalyst capable of improving sulfur tolerance and regeneration capacity, a preparation method and application thereof, the components of the catalyst comprise a completely hydroxylated gamma-Al2O3 carrier, a catalytic active component and a catalytic promoter, the catalytic active component comprises noble metal Pd, and the catalytic promoter comprises at least one of ZrO2, CeO2 or TiO2; according to the technical scheme, the catalyst additive is added into the alumina-loaded Pd, so that low-temperature decomposition of sulfur is promoted, the sulfur resistance and regeneration capacity of Pd active sites can be remarkably improved, and the catalyst additive is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of catalyst preparation, and specifically relates to a methane oxidation catalyst with improved sulfur resistance and regeneration capability, a preparation method and its application, and specifically can be applied to a lean-burn natural gas engine exhaust purification system. Background Art

[0002] The high fuel efficiency and low emissions of natural gas engines compared to gasoline and diesel make natural gas (which consists primarily of methane) a cleaner energy source, especially for transportation. However, methane is a potent greenhouse gas with a global warming potential (GWP) of approximately 86 times that of carbon dioxide on a 100-year timescale. Lean-burn engines offer significant opportunities to reduce nitrogen oxide and greenhouse gas emissions (up to 21%) due to their higher fuel efficiency compared to gasoline and diesel engines. However, this emission reduction potential can be offset by the emission of unburned methane (methane slip) due to their higher GWP. Therefore, it is necessary to fully reduce methane emissions to achieve full utilization of natural gas as a transportation fuel and comply with increasingly stringent emission control policies. After decades of research, palladium-based catalysts remain the most active catalysts for methane oxidation.

[0003] The Pd(101) surface is the main source of low-temperature activity, via dissociative adsorption of methane onto undercoordinated Pd sites on the plane. In addition to the presence of moisture and low-temperature exhaust gases, the presence of sulfur, primarily in the form of SO2, is one of the major challenges in developing efficient catalysts for methane abatement. Sulfur compounds are severe poisons for methane oxidation catalysts, even when present in small amounts (1 ppm) under reaction conditions. For Pd-based catalysts, sulfur poisoning occurs via the conversion of active PdO sites to less active PdO-SOx sites. The mechanism of deactivation of active Pd(101) during methane oxidation in the presence of SOx is investigated using DFT calculations. Under experimentally relevant conditions, the formation of SO4-modified Pd(101) is favored, which results in the blocking of coordinatively unsaturated Pd atoms in Pd(101), which are essential for methane oxidation. Furthermore, it is well known that the co-presence of moisture and sulfur accelerates the deactivation of Pd-based catalysts via the formation of inactive sulfides.

[0004] CN114950422A discloses a methane oxidation catalyst and its preparation method and application. The catalyst uses Al2O3 as a carrier, and the catalytic active components include Pt-doped PdO nanocrystals, and any one or a combination of at least two of La, Pr, Y or Nd as a catalytic promoter. However, the content of each component has an important influence on the performance. Too high or too low will affect the activity and stability of the catalyst. In addition, the catalyst evaluation atmosphere does not contain sulfur, and is not suitable for the catalytic oxidation of methane in sulfur-containing lean-burn natural gas vehicle exhaust.

[0005] CN114258322A discloses a Ru-Pt / ZrO2 sulfur-resistant methane oxidation catalyst, which has high activity and excellent sulfur resistance, but uses a large amount of precious metals (such as ruthenium accounting for 0.1-20wt% of the total mass of the catalyst); and when Ru is heated to above 450°C in air, it will slowly oxidize to generate slightly volatile ruthenium dioxide, which seriously affects the durability of the catalyst.

[0006] CN116899562A discloses a methane combustion catalyst with improved sulfur resistance, which uses cordierite ceramic carrier as a matrix, precious metals Pt and Pd, cerium aluminum composite oxide and binder aluminum sol as a bottom layer, and 99% Al2O3 and 1% pseudo-boehmite as an upper coating. The catalyst has a low methane ignition temperature, high methane conversion activity and can delay the poisoning effect of sulfur dioxide on the catalyst. However, the cost of the catalyst is relatively high, and the preparation process is complicated, which is not conducive to the industrial production of the catalyst. Summary of the invention

[0007] In view of the above-mentioned deficiencies in the prior art, the present application provides a methane oxidation catalyst with improved sulfur resistance and regeneration ability, which is suitable for industrial production by adding a catalyst promoter to Pd supported on alumina to promote the low-temperature decomposition of sulfur, thereby significantly improving the sulfur resistance and regeneration ability of Pd active sites.

[0008] In order to solve the above technical problems, the technical solution adopted in the present application is: a methane oxidation catalyst with improved sulfur resistance and regeneration ability, the components of the catalyst include a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, the catalytically active component contains the precious metal Pd, and the catalytic promoter contains at least one of ZrO2, CeO2 or TiO2.

[0009] Furthermore, the completely hydroxylated γ-Al2O3 carrier is obtained by subjecting the γ-Al2O3 carrier to complete hydroxylation treatment and then drying it at 90°C overnight.

[0010] Furthermore, the content of at least one of the catalyst promoter (promoter) ZrO2, CeO2 or TiO2 accounts for 4%-20% of the total mass of the methane oxidation catalyst, that is, the content of the overall catalyst promoter in the methane oxidation catalyst.

[0011] Furthermore, the content of at least one of the catalytic promoter (promoter) ZrO2, CeO2 or TiO2 accounts for 4%, 8%, 12% or 20% of the total mass of the methane oxidation catalyst, that is, the content of the overall catalytic promoter in the methane oxidation catalyst.

[0012] Furthermore, the content of the noble metal Pd in ​​the catalytically active component, calculated as a single substance, accounts for 0.5-1.5% of the total mass of the methane oxidation catalyst.

[0013] The present application also provides a method for preparing the above-mentioned methane oxidation catalyst with improved sulfur resistance and regeneration ability, the steps of which include:

[0014] (1) Preparation of fully hydroxylated γ-Al2O3 support: γ-Al2O3 was added to ammonia water and dried at 85-95°C overnight to ensure that the alumina support was fully hydroxylated;

[0015] (2) Preparation of catalyst promoter-Al2O3 (bimetallic oxide): using a reflux condenser, the fully hydroxylated alumina carrier obtained in step (1) is placed in a reactor, and then anhydrous ethanol is added to mix; anhydrous ethanol is added to a centrifuge tube, and then the catalyst promoter precursor solution is titrated into the centrifuge tube; cooling water is passed through the condenser, and the temperature of the heating jacket is set to 75-85°C and the rotation speed is 350-450rpm; when the temperature in the reactor reaches 78-82°C, the liquid in the centrifuge tube is slowly dripped into the reactor, and after dripping, anhydrous ethanol is added to the centrifuge tube for rinsing and then titrated; after reacting for 1.5-2.5 hours, the condenser is removed to evaporate the ethanol, and the obtained dry powder is dried at room temperature overnight, and then calcined at 550-650°C for 3-5h, with a heating rate of 2-5°C / min, to obtain a composite oxide, namely, catalyst promoter-Al2O3;

[0016] (3) Preparation of supported metallic palladium: Tetraamine palladium (II) nitrate solution (tetraamine palladium (II) nitrate, CAS13601-08-6) is mixed and diluted with ultrapure water by a wet impregnation method, and then added to the composite oxide prepared in step (2), and then ultrapure water is dropped, the resulting mixture is stirred, and then evaporated to dryness at 75-85°C, and the resulting dry powder is calcined at 450-550°C at a temperature gradient of 2-5°C / min for 4-6h to obtain a methane oxidation catalyst.

[0017] Furthermore, the bimetallic oxide described in step (3) is calcined at 600° C. for 4 h with a heating rate of 3° C. / min.

[0018] Furthermore, the calcination in step (4) is carried out at 500° C. and a temperature gradient of 3° C. / min for 5 h.

[0019] The present application also provides an application of the above-mentioned methane oxidation catalyst with improved sulfur resistance and regeneration ability, which is specifically applied to a lean-burn natural gas engine exhaust purification system.

[0020] Compared with the prior art, this application has the following beneficial effects:

[0021] 1. Compared with the traditional Pd / Al2O3 catalyst, the methane oxidation catalyst prepared in the present application significantly improves the sulfur resistance and regeneration ability of the prepared catalyst by adding a promoter. Under dry reaction conditions, the surface sulfate formed in the presence of the catalytic promoter is easily decomposed under the reaction conditions, thereby completely restoring the activity of the poisoned catalyst. The results of the regeneration study showed that the rich reducing methane atmosphere can fully regenerate the catalyst promoted by the catalytic promoter, the Pd nanoparticles are obviously sintered, and the activity of Pd / Al2O3 is significantly restored. The results of the cyclic poisoning and regeneration tests showed that although sulfur accumulation will affect the regeneration efficiency of Pd / Al2O3, the presence of the catalytic promoter can enable the sulfur species to continue to effectively decompose, thereby effectively restoring the activity after the poisoning and regeneration cycles.

[0022] 2. The methane oxidation catalyst prepared in the present application uses only a single Pd precious metal as an active component and adopts a wet impregnation preparation method, with a low loading content and a simple process flow.

[0023] 3. The methane oxidation catalyst of the present application can be applied to water- and sulfur-containing lean-burn natural gas vehicle exhaust gas and has good application prospects.

[0024] 4. The technical solution of the present application uses ZrO2, CeO2 or TiO2 as a catalytic aid, i.e., a promoter, and then experiments on the individual effects of sulfur poisoning and regeneration of aluminum-supported Pd catalysts under aqueous and anhydrous conditions, so as to clearly understand the inhibitory or enhancing effects of these promoters, and provide a methane oxidation catalyst with improved sulfur resistance and regeneration capabilities; the results of this work provide insights into how promoters affect sulfur poisoning and regeneration of methane oxidation catalysts, which is of great significance to the practical design of industrially relevant catalysts.

[0025] 5. The catalyst carrier of the present application is a fully hydroxylated γ-Al2O3 carrier, which is prepared by doping γ-Al2O3 (99.9% metal basis) into aqueous ammonia (28-30% NH3 basis) and drying at 85-95°C overnight to ensure that the alumina carrier is fully hydroxylated, thereby providing sufficient hydroxyl groups for surface reaction with the promoter alkoxide precursor. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : XRD spectra of original Pd / Al2O3 and Ce, Ti, and Zr modified catalysts.

[0027] Figure 2 : (a) Ti 2p region of Pd / TiAl catalyst; (b) Zr 3d region of Pd / ZrAl catalyst.

[0028] Figure 3: In situ infrared diffuse reflectance results of CO on Pd / Al2O3, Pd / ZrAl, Pd / CeAl and Pd / TiAl after CO saturation and vacuum at room temperature (the results show that there are different types of Pd on the catalyst).

[0029] Figure 4 : The Pd / Al2O3 catalyst was dried and reacted at 400°C for 10 hours under 5ppm SO2 conditions, and the methane conversion rate over time (decreased with increasing time); reaction conditions: CH4 (0.2%), O2 (10%), 5ppm SO2, N2 balance, GHSV: 120,000ml.g -1 .h -1 .

[0030] Figure 5 :Effect of ZrO2 loading on the deactivation of supported PdO catalyst after drying at 400℃ for 10 hours under 5ppm SO2 conditions (indicating that the methane conversion rate decreases with time); reaction conditions: CH4 (0.2%), O2 (10%), 5ppm SO2, N2 balance, GHSV: 120,000ml.g -1 .h -1 .

[0031] Figure 6 :Effect of CeO2 loading on the deactivation of supported PdO catalyst after drying at 400℃ for 10 hours under 5ppm SO2 (indicating that the methane conversion rate decreases with time); reaction conditions: CH4 (0.2%), O2 (10%), 5ppm SO2, N2 balance, GHSV: 120,000ml.g -1 .h -1 .

[0032] Figure 7 :Effect of TiO2 loading on the deactivation of supported PdO catalyst after drying at 400℃ for 10 hours under 5ppm SO2 (indicating that the methane conversion rate decreases with time); Reaction conditions: CH4 (0.2%), O2 (10%), 5ppm SO2, N2 balance, GHSV: 120,000ml.g -1 .h -1 .

[0033] Figure 8 :CH4 ignition curves (showing the comparison of fresh catalyst and regenerated catalyst after SO2 poisoning under wet reaction conditions) (a) Pd / Al2O3 (b) Pd / ZrAl (c) Pd / CeAl and (d) Pd / TiAl; reaction conditions: CH4 (0.2%), O2 (10%), H2O (5%), N2 balance, GHSV: 120,000ml.g-1 .h -1 , under wet lean reaction conditions; R is the regenerated catalyst after SO2 poisoning, which is regenerated in a wet rich reaction gas without O2.

[0034] Fig. 9 : Effect of SO2 on methane conversion over (a) Pd / Al2O3 (b) Pd / ZrAl (c) Pd / CeAl and (d) Pd / TiAl catalysts under dry conditions; Reaction conditions: CH4 (0.2%), O2 (10%), H2O (5%, in the presence of), N2 balance, SO2 (5ppm, in the presence of), GHSV: 120,000ml.g -1 .h -1 ; (D-dry conditions; DS-drying in the presence of SO2; M-wet conditions in the presence of moisture; MS-wet conditions in the presence of moisture and SO2).

[0035] Fig.10 : SO2 DRIFTS spectra obtained after the catalyst was exposed to 20 ppm SO2 at 300°C for 60 min under (a) dry reaction and (b) wet reaction conditions; showing the effect of the promoter on the distribution of sulfur species formed on the catalyst; DRIFTS environment: CH4 (0.2%), O2 (10%), N2 balance, SO2 (20 ppm), H2O (2%). All spectra are on the same scale.

[0036] Fig.11 :CH4 ignition curves: showing the effect of promoter on SO2 poisoning regeneration under dry conditions for (a) Pd / Al2O3 (b) Pd / ZrAl (c) Pd / CeAl and (d) Pd / TiAl catalysts. Reaction and regeneration conditions: CH4 (0.2%), O2 (10%), N2 balance, SO2 (5ppm), GHSV: 120,000ml.g -1 .h -1 ; R1 is the regeneration run, and R2 is the second run after regeneration, which is used to evaluate the activity recovery.

[0037] Fig.12 :The catalyst was isothermally sulfided at 450℃ in the presence of water, and the effect of regeneration technology on activity recovery was studied; sulfidation conditions: CH4 (0.2%), O2 (10%), N2 balance, H2O (5%), SO2 (10ppm), GHSV: 120,000ml.g -1 .h -1D: Dry reaction conditions (0.2% CH4, 10% O2 and N2 in balance). M: Wet reaction conditions (0.2% CH4, 10% O2, 5% H2O and N2 in balance). R1: Regeneration in a wet reaction mixture at 600°C in the absence of SO2. R2: Wet reduction regeneration (0.2% CH4, 5% H2O and N2 in balance at 550°C for 30 minutes).

[0038] Fig.13 :(a) Comparison of methane ignition activity of regenerated catalysts with fresh Pd / Al2O3 as reference (b) Cyclic SO2 poisoning and regeneration of Pd / Al2O3 and Pd / ZrAl catalysts at 500℃. Sulfidation conditions: CH4 (0.2%), O2 (10%), N2 balance, H2O (5%), SO2 (10ppm), GHSV: 120,000ml.g -1 .h -1 R: Rich regeneration (0.2% CH4, 5% H2O and N2 balance, 500℃, 30 minutes), M: Wet lean reaction conditions (0.2% CH4, 10% O2, 5% H2O, N2 balance)

[0039] Fig.14 In situ CO-DRIFTS of fresh and regenerated catalysts showing the effect of promoters on the regeneration of SO2-poisoned catalysts and the availability of Pd sites for CO adsorption after regeneration on (a) Pd / Al2O3 (b) Pd / ZrAl (c) Pd / CeAl (d) Pd / TiAl. F-fresh catalyst and R-regenerated catalyst. DETAILED DESCRIPTION

[0040] In order to better explain the present application and understand the technical solution of the present application, the present application is further described in detail below. However, the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0041] The catalyst of the present application, in addition to the main components active ingredients and catalytic aids, the remainder is a completely hydroxylated γ-Al2O3 carrier and inevitable trace impurities in the catalyst, etc.; the various raw materials used in the embodiments of the present application are all commercially available raw materials without special explanation.

[0042] Embodiment 1:

[0043] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is ZrO2, and the mass fraction of zirconium oxide is 8%.

[0044] The preparation method of the above-mentioned methane oxidation catalyst comprises the following steps:

[0045] (1) Preparation of fully hydroxylated γ-Al2O3 support: 20.5 g of γ-Al2O3 (99.9% metal basis) was added to 35 ml of aqueous ammonia (28-30% NH3 basis) and dried at 90°C overnight to ensure that the alumina support was fully hydroxylated and provided sufficient hydroxyl groups for surface reaction with the promoter alkoxide precursor.

[0046] (2) Preparation of ZrO2-Al2O3: Using a reflux condenser, 1.84 g of a fully hydroxylated alumina carrier was placed in a three-necked flask and 10 ml of anhydrous ethanol was added; 10 ml of anhydrous ethanol was added to a centrifuge tube, and 0.623 g of zirconium n-butoxide (CAS No.: 1071-76-7, where zirconium n-butoxide is a precursor solution of ZrO2, purchased from Sigma Research Reagents; or other commercially available zirconium n-butoxide products are suitable for this application, such as those shown in the website https: / / www.aladdin-e.com / zh_cn / z106334.html) was titrated into the centrifuge tube; cooling water was passed into the condenser, and the heating jacket was set to a temperature of 80°C and a rotation speed of 400 rpm. When the temperature in the three-necked flask reaches 80°C, the liquid in the centrifuge tube is slowly dripped into the three-necked flask, and after dripping, 5 ml of anhydrous ethanol is added to the centrifuge tube for rinsing and then titration; after 2 hours, the condenser is removed to evaporate the ethanol, and the obtained dry powder is dried at room temperature overnight, and then calcined at 600°C for 4 hours with a heating rate of 3°C / min (the mass fraction of ZrO2 in the catalyst is 8wt%) to obtain a zirconium-aluminum composite oxide;

[0047] (3) Preparation of supported metal palladium: 0.34 g of tetraamine palladium (II) nitrate solution (CAS No.: 13601-08-6, where the tetraamine palladium (II) nitrate solution is a precursor solution of Pd, purchased from Sigma Research Reagents; or other commercially available tetraamine palladium (II) nitrate solution products are suitable for this application, such as the one shown in the website https: / / www.sigmaaldrich.cn / CN / en / product / aldrich / 423823) was diluted with 10 ml of ultrapure water and added to 1.188 g of zirconium aluminum composite oxide, and then 15 ml of ultrapure water was dropped into it. The resulting mixture was stirred for 1 hour, and then evaporated and dried at 80°C to obtain a dry powder; the resulting dry powder was calcined at 500°C at a temperature gradient of 3°C / min for 5 hours (the mass fraction of Pd in ​​the catalyst is 1 wt%) to obtain a methane oxidation catalyst.

[0048] Embodiment 2:

[0049] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is ZrO2, and the mass fraction of zirconium oxide is 4%.

[0050] The preparation method is the same as that in Example 1, except that the mass fraction of ZrO2 in step (2) is adjusted to 4%.

[0051] Embodiment 3:

[0052] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is ZrO2, and the mass fraction of zirconium oxide is 12%.

[0053] The preparation method is the same as that in Example 1, except that the mass fraction of ZrO2 in step (2) is adjusted to 12%.

[0054] Embodiment 4:

[0055] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is ZrO2, and the mass fraction of zirconium oxide is 20%.

[0056] The preparation method is the same as that in Example 1, except that the mass fraction of ZrO2 in step (2) is adjusted to 20%.

[0057] Embodiment 5:

[0058] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is TiO2, and the mass fraction of titanium oxide is 4%.

[0059] The preparation method refers to the preparation method in Example 1, except that the catalyst ZrO2 in step (2) is replaced by TiO2, and butyl titanate (CAS No.: 5593-70-4, butyl titanate here is a precursor solution of TiO2, purchased from Sigma Research Reagents; or other commercially available butyl titanate products are suitable for this application, such as those shown in the website https: / / www.sigmaaldrich.cn / CN / en / product / aldrich / 244112) is used as a precursor, and the mass fraction of TiO2 is 4%.

[0060] Embodiment 6:

[0061] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is TiO2, and the mass fraction of titanium oxide is 8%.

[0062] The preparation method is the same as that in Example 1, except that the catalyst promoter ZrO2 in step (2) is replaced by TiO2, butyl titanate is used as a precursor, and the mass fraction of TiO2 is 8%.

[0063] Embodiment 7:

[0064] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is TiO2, and the mass fraction of titanium oxide is 12%.

[0065] The preparation method is the same as that in Example 1, except that the catalyst promoter ZrO2 in step (2) is replaced by TiO2, butyl titanate is used as a precursor, and the mass fraction of TiO2 is 12%.

[0066] Embodiment 8:

[0067] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is TiO2, and the mass fraction of titanium oxide is 20%.

[0068] The preparation method is the same as that in Example 1, except that the catalyst promoter ZrO2 in step (2) is replaced by TiO2, butyl titanate is used as a precursor, and the mass fraction of TiO2 is 20%.

[0069] Embodiment 9:

[0070] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is CeO2, and the mass fraction of cerium oxide is 4%.

[0071] The preparation method refers to steps (1) and (3) in Example 1, and step (2) is changed to: using the initial wetness method, cerium nitrate (CAS No.: 10294-41-4, cerium (III) nitrate hexahydrate here is the precursor solution of CeO2, purchased from Sigma Research Reagents; or other commercially available cerium (III) nitrate hexahydrate products are suitable for this application as CeO2 precursors, to prepare a CeO2-modified alumina carrier (CeO2 loading of 4%).

[0072] Embodiment 10:

[0073] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is CeO2, and the mass fraction of cerium oxide is 8%.

[0074] The preparation method refers to steps (1) and (3) in Example 1, and step (2) is changed to: using the incipient wetness method, cerium (III) nitrate hexahydrate as the CeO2 precursor, a CeO2-modified alumina carrier (CeO2 loading is 8%) is prepared.

[0075] Embodiment 11:

[0076] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is CeO2, and the mass fraction of cerium oxide is 12%.

[0077] The preparation method refers to steps (1) and (3) in Example 1, and step (2) is changed to: using the initial wetness method, cerium (III) nitrate hexahydrate as the CeO2 precursor, a CeO2-modified alumina carrier (CeO2 loading is 12%) is prepared.

[0078] Embodiment 12:

[0079] A methane oxidation catalyst with improved sulfur resistance and regeneration ability comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the active component is the precious metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%; the catalytic promoter is CeO2, and the mass fraction of cerium oxide is 20%.

[0080] The preparation method refers to steps (1) and (3) in Example 1, and step (2) is changed to: using the initial wetness method, cerium (III) nitrate hexahydrate as the CeO2 precursor, a CeO2-modified alumina carrier (CeO2 loading is 20%) is prepared.

[0081] Comparative Example 1:

[0082] A methane oxidation catalyst comprises a γ-Al2O3 carrier and a catalytically active component, wherein the active component is the noble metal Pd, and the mass fraction of Pd in ​​the catalyst is 1%.

[0083] The preparation method is the same as that in Example 1, except that steps (1) and (2) in Example 1 are not performed, but metallic palladium is directly loaded on a commercial alumina carrier.

[0084] The catalysts obtained in the above examples and comparative examples were tested and characterized for their performance:

[0085] Catalyst characterization

[0086] Powder x-ray diffraction (XRD) patterns of the catalysts were collected on a Bruker D8 Advance with a diffraction scan range of 5 to 90° and a step size of 0.01°C. XPS analysis of fresh and regenerated catalysts was performed on a Thermo Scientific ESCALAB Xi+ instrument with an Al Kα source gun. The pass energy was 30 eV and the energy step size was 0.05 eV. All spectra were charge corrected using incidental carbon at 284.8 eV. HR / TEM images were collected on a FEI Tecnai G2 F20 S-TWIN at 200 kV. The size of an average of 100 particles was counted and measured to determine the average particle size of the palladium nanoparticles. Elemental mapping of the regenerated catalyst was performed with the aid of an Oxford X-Max 80T to observe the presence of residual sulfur after regeneration. Bulk elemental analysis was performed on an ICP (PerkinElmer Avio 200) instrument to determine the actual / experimental loading of Pd on the catalyst.

[0087] CO-DRIFTS was performed to determine the type and nature of Pd species on the surface of original Pd / Al2O3 and modified Pd / ZrAl, Pd / CeAl and Pd / TiAl catalysts. CO-DRIFTS analysis was performed on a Nicolet 6700FTIR instrument (Thermo Fischer) equipped with a liquid nitrogen cooled MCT detector and a PrayingMantis in-situ cell. The catalyst was first pretreated in N2 (30 ml / min) at 200°C for 30 minutes to remove surface adsorbed species. Subsequently, the catalyst was cooled to room temperature and exposed to a 3% CO / N2 gas mixture for 10 minutes. Before collecting the DRIFT spectrum, the sample was evacuated into N2 to remove excess CO in the system.

[0088] SO2–DRIFTS was performed on the same equipment as CO–DRIFTS to determine the effect of the promoter on the type and nature of sulfur species formed on the catalyst under dry and wet reaction conditions. In a typical experiment, the catalyst was first mixed with KBr (1:1) and pretreated in N2 at 200°C for 30 min. The in situ cell temperature was raised to the desired temperature and a background scan was collected before collecting the DRIFT spectrum after exposing the catalyst to a dry reaction gas containing CH4 (0.2%), O2 (10%), SO2 (20 ppm), balanced by N2 for 60 min. Similar experiments were performed in a wet reaction mixture containing 2% H2O to investigate the role of moisture on the type and distribution of sulfur species. The effect of temperature was investigated under dry and wet reaction conditions. Normalized spectral data are presented for effective comparison of catalysts.

[0089] Table 1: Gas mixtures used for activity evaluation, catalyst poisoning and regeneration experiments

[0090]

[0091] Catalyst Evaluation

[0092] 1) Activity evaluation and catalyst deactivation in dry and wet SO2 reaction atmospheres

[0093] Experiments were conducted under dry and wet conditions to evaluate the effect of the promoter on the SO2 deactivation / resistance of the catalyst. The effect of SO2 poisoning on the catalytic activity (ignition) of the catalyst in the absence of moisture was evaluated by introducing 5 ppm SO2 into the dry reaction mixture (RM3). Subsequently, the catalyst was deactivated at 400°C for 10 hours in the presence of 5 ppm SO2 under dry conditions (RM3). The combined effect of SO2 and moisture on the ignition performance of the catalyst was studied by introducing 5 ppm SO2 and 5% H2O into the reaction mixture (RM4). Accelerated catalyst deactivation experiments were performed by passing 10 ppm SO2 and 5% H2O into the reaction mixture at 450°C for 4 hours (RM5).

[0094] 2) Regeneration of SO2 poisoned catalyst

[0095] The catalyst sample deactivated in the dry reaction mixture (RM3 containing 5 ppm SO2 for 10 hours) was regenerated by performing two consecutive cycles of ignition experiments in the dry reaction mixture without SO2 (RM1). The first run served as a regeneration step, while the second run was used to evaluate the extent of catalyst regeneration. The two regeneration steps were used to study the regeneration of the catalyst poisoned in the presence of 10 ppm SO2 and 5% H2O (RM5). The first regeneration step involved heating the catalyst to 600°C for 30 minutes in a wet lean reaction atmosphere (RM2). The second regeneration step was to place the catalyst in a wet reducing methane atmosphere (RM6) for 30 minutes, followed by an activity evaluation at 450°C (by comparing the conversion of methane before and after SO2 poisoning at the same temperature), and then an ignition test of the regenerated catalyst in a wet lean reaction atmosphere without SO2 (RM2).

[0096] Physicochemical properties

[0097] XRD pattern ( Figure 1 ) showed that, in addition to the broad XRD pattern of γ-Al2O3 (JCPDS29-1486), a 33.8° reflection corresponding to the (101) plane of PdO (JCPDS 43-1024) was observed on all catalysts. Although reflections corresponding to cubic structured CeO2 (JCPDS 34-0394) were observed in the XRD pattern of Pd / CeAl, indicating that CeO2 existed in a crystalline state, reflections corresponding to titania and zirconia were not observed on Pd / TiAl and Pd / ZrAl catalysts, indicating that they existed in an amorphous state. Nevertheless, the Ti2P3 / 2 (BE 458.6 eV) and Zr3d5 / 2 (BE 182.6 eV) XPS peaks of Pd / TiAl and Pd / ZrAl catalysts ( Figure 2 ) indicates that they all exist in the form of oxides.

[0098] Using in situ CO DRIFTS ( Figure 3 ) obtained information on the structure of Pd particles on fresh catalysts. The infrared spectrum of CO adsorption vibration showed that CO at 2080 cm -1 , 1978 and 1945–1864cm -1 There is an absorption peak at 2100–2080cm -1 The infrared bands at 1970 cm-1 are attributed to the linear adsorption of CO at the corners and edges of Pd NPs. -1 The bands are derived from the bridge adsorption of CO on the step sites of Pd particles, while the 1945–1864 cm -1The peaks between are related to the adsorption of CO on the bridge sites and hollow sites of Pd. Compared with the original Pd / Al2O3 catalyst, the bridging CO peak (about 1920 cm -1 ) indicates that the adsorption environment of Pd has changed, which may be due to its interaction with the promoter. From the above results, any difference in the behavior of Pd active sites relative to pristine Pd / Al2O3 may originate from the interaction of Pd with the co-catalyst.

[0099] Evaluating the Effect of Promoters on Sulfur Poisoning of Methane Oxidation Catalysts under Dry and Wet Reaction Conditions

[0100] For simplicity, since the catalysts containing 8 wt% promoter loading (hereinafter referred to as Pd / TiAl, Pd / CeAl and Pd / TiAl) showed comparable methane conversion performance (see Table 2), we focused on these catalysts when evaluating the effects of promoters on the sulfidation and regeneration of supported Pd catalysts.

[0101] Table 2: Effect of promoter loading on catalytic methane oxidation in the presence of 5 ppm SO2 under dry conditions

[0102]

[0103]

[0104] D – Dry reaction environment

[0105] DS – 5 ppm SO2 in dry environment.

[0106] like Fig. 9 As shown in Figure 2, different promoters have different effects on the catalytic activity of the catalyst in the presence of SO2 and water. Under dry reaction conditions in the presence of SO2, the original Pd / Al2O3 only showed a slight decrease in activity in the ignition curve ( Fig. 9 a). After adding ZrO2, the sulfur resistance of Pd / ZrAl catalyst under dry conditions was significantly improved, while the catalytic performance did not change significantly ( Fig. 9 b). However, the addition of CeO2 and TiO2 to Al2O3 resulted in a significant decrease in the catalytic performance in the presence of SO2 under dry conditions ( Fig. 9 c and 9d). This indicates that while ZrO2 enhances the sulfur resistance of the catalysts under dry conditions, adverse effects are observed in the presence of CeO2 and TiO2 promoters.

[0107] To further explore this phenomenon, the applicant examined the effect of the promoter loading on the sulfur resistance of the catalyst. Under dry conditions, the changes in the catalytic performance of all ZrO2 promoters in the presence of SO2 were negligible (Table 2). In contrast, with the increase in CeO2 and TiO2 loading, the catalytic performance deteriorated further, further confirming the respective effects of ZrO2, CeO2 and TiO2 on the sulfur resistance of the promoter. Subsequently, the catalyst was subjected to long-term sulfurization for 10 hours (100 ppm) at 400 ° C in the presence of 5 ppm SO2 under dry conditions. Figure 4-7 ). Consistent with the ignition curve, the original Pd / Al2O3 ( Figure 4 ) and ZrO2 modified catalysts ( Figure 5 ) showed a slower deactivation rate, while CeO2 modified ( Figure 6 ) and TiO2 modified catalysts ( Figure 7 ) deactivation rate is faster and increases with the co-catalyst loading. The increase in deactivation rate with increasing CeO2 and TiO2 loadings suggests that these co-catalysts provide more sites for SO2 adsorption and formation of sulfur species, which can easily overflow and deactivate the active Pd sites, probably by forming PdSO4 and destroying the support's ability to activate and transfer oxygen species to Pd for methane oxidation.

[0108] Next, the applicant explored the effect of the promoter under conditions closer to actual application (i.e., in the presence of moisture and SO2). First, in the presence of moisture alone, the reaction temperature of all catalysts increased compared to the corresponding activity under dry conditions ( Fig. 9 and T50 and T90 values ​​in Table 3). Moisture is known to have a reversible inhibitory effect on PdO catalysts for methane oxidation, especially at temperatures below 450 °C. This partially reversible deactivation has been attributed to surface coverage of Pd active sites by water and competitive adsorption and activation by H2O, leading to hydroxylation of Pd and the support. These hydroxyls restrict access to under-coordinated Pd active sites and inhibit activation and migration of oxygen on the support. Although all catalysts were reversibly deactivated in the presence of moisture (up to 600 °C, Fig. 9 ) all showed stable activity, but the Pd / TiAl catalyst seemed to suffer from moisture-induced deactivation above 500 °C (as evidenced by the decrease in methane conversion above 500 °C), even though it was stable in this temperature range under dry conditions ( Fig. 9 d).

[0109] Table 3: Effect of SO2 and water on catalyst T 50 Impact

[0110] catalyst <![CDATA[T 50 (℃)D]]> <![CDATA[T 90 (℃)D]]> <![CDATA[T 50 (℃)M]]> <![CDATA[T 90 (℃)M]]> <![CDATA[T 50 (℃)MS]]> <![CDATA[T 90 (℃)MS]]> <![CDATA[Pd / Al2O3]]> 340 415 414 478 458 529 Pd / ZrAl 366 437 417 475 442 493 Pd / CeAl 365 456 425 492 470 561 Pd / TiAl 368 443 416 484 474 NA

[0111] D stands for dry conditions

[0112] M represents moist conditions where moisture is present

[0113] MS represents the presence of moisture and SO2

[0114] NA: Not Available - T90 not achieved.

[0115] like Fig. 9 a and Fig. 9 As shown in Figure 3, the combined effect of moisture and SO2 on the activity inhibition is affected by the presence of the promoter. Although both Pd / Al2O3 and Pd / ZrAl showed comparable activity in the presence of moisture (Table 3), the activity of Pd / ZrAl was significantly higher than that of Pd / Al2O3 in the presence of moisture and SO2. At the same time, higher inhibition effects were observed on Pd / CeAl and Pd / TiAl catalysts.

[0116] Study on SO2 DRIFTS under dry and wet reaction conditions

[0117] Considering the different behaviors of PdO active sites on the promoter in the presence of SO2, applicants speculate that the promoter affects the type and distribution of sulfur species on the catalyst. Fig.10 Representative normalized in situ DRIFTS spectra are shown for samples exposed to a dry ( Fig.10 a) and wet ( Fig.10 b) Various sulfur species formed after 60 min in the reaction mixture. 850–1100 cm -1 The area between can be attributed to the adsorption of sulfite (SO3 2- ), while the adsorbed sulfate (SO4 2- ) stretching movement results in 1100–1300cm -1 Peak between 1040cm -1 The peaks around are attributed to sulfite species. Two peaks corresponding to sulfate species were observed (at 1268 and 1160 cm -1 1200cm -1 Sulfate species above 1200 cm are attributed to surface sulfates with covalent character, while those below 1200 cm -1 The sulfate species are blocky sulfates with more ionic character. 1420 and 1225–1268 cm -1 The peaks around 1345 cm-1 are attributed to the stretching vibration of the surface sulfate with tridentate surface coordination, while the peaks at 1345 and 1160 cm-1 are attributed to the stretching vibration of the surface sulfate with tridentate surface coordination. -1 The peaks around are associated with the expansion and contraction of bulk bidentate sulfates. This attribution is supported by the fact that these sulfate species are Fig.10b) showed different behaviors in the presence of SO2. It is worth noting that although obvious catalyst deactivation was observed in the presence of SO2 ( Figure 4-7 ), but no peak corresponding to PdSO4 was observed in DRIFTS, which may be due to the low Pd loading (1 wt%) used in this application.

[0118] The type of promoter affects the type and strength of sulfur species formed on the catalyst. Fig.10 a), except for the 1268 cm- -1 In addition to the surface sulfate peak at 1225 cm, an additional strong surface sulfate peak (~1225 cm) was observed on Pd / CeAl and Pd / TiAl samples. -1 ), which only appears as a weak shoulder on the Pd / ZrAl sample. In addition, relative to Pd / Al2O3, a peak at 1161 cm was observed on Pd / CeAl and Pd / TiAl. -1 The more intense peak associated with bulk sulfate is observed on Pd / ZrAl, while it is weakened on Pd / ZrAl, indicating that less bulk sulfate is formed on the ZrO2-modified catalyst. This suggests that in addition to providing additional sites for surface sulfate formation, the presence of CeO2 and TiO2 favors the formation of more bulk sulfate, which explains the increase in SO2 deactivation with increasing CeO2 and TiO2 loadings ( Figure 5-7 ). In addition, this observation may also explain why the ZrO2-modified catalysts exhibited higher sulfur resistance under dry conditions.

[0119] The presence of water seems to favor the formation of bulk species at the expense of surface sulfate species, which is more obvious and prevalent on Pd / CeAl and Pd / TiAl catalysts ( Fig.10 b) This can be seen from the reduction in the intensity of the surface sulfate peaks, especially at ~1225 cm -1 The intensity peak at is attributed to the sulfate formed on CeO2 and TiO2, which is accompanied by Fig.10 The massive sulfate peak (1161 cm -1 ). This observation is supported by previous isotopic trace studies on the sulfidation of metal oxides, which showed that moisture promotes the transformation of tridentate surface sulfates to bidentate bulk sulfates. However, it should be noted that only a slight increase in the intensity of bulk sulfates was observed on Pd / ZrAl and pristine Pd / Al2O3 catalysts, suggesting that stable sulfates are more easily formed on TiO2 and CeO2 modified catalysts in the presence of moisture.

[0120] The practical significance of this observation is that the presence of water leads to the formation of more stable bulk materials, especially in the presence of CeO2 and TiO2 under dilute wet conditions, which are widely used as methane oxidation catalysts. This could explain why a more pronounced SO2-induced inhibition of catalytic activity was observed under wet conditions than under dry conditions ( Fig. 9 , Table 4). In addition to the previously reported effects of moisture (including surface coverage / competitive adsorption of moisture on Pd active sites, Pd / support hydroxylation, and hindering SO2 spillover from PdO to the support), applicants observed here that moisture promotes the formation of more stable bulk sulfates, which may hinder the movement of oxygen from the support and promote sulfur spillover to the active sites, thereby destroying the synergistic interaction between the support and the active sites. This may explain why TiO2 and CeO2 cocatalysts are more susceptible to SO2 inhibition / deactivation than pristine and ZrO2 cocatalysts.

[0121] Effect of promoters on catalyst regeneration under wet conditions

[0122] Considering the observed combined effects of moisture and SO2 on methane oxidation over the catalyst ( Fig. 9 ), the applicant isothermally deactivated the catalyst at 450°C in the presence of 5% H2O and 10ppm SO2 ( Fig.12 ). Before deactivating the catalysts, they were first exposed to a dry-wet-dry reaction mixture. Regardless of the catalyst composition, the observed slight moisture-induced deactivation was reversible at high reaction temperatures (450 °C in this case) (see Fig.12 region D1–M1–D2 in a), possibly through surface dehydroxylation and subsequent Pd active sites available for CH4 dissociation.

[0123] Fig.12 The regional MS of a shows that the presence of the promoter seems to affect the sulfidation behavior of the catalyst. Although both pristine Pd / Al2O3 and Pd / ZrAl show similar deactivation trends, faster deactivation rates are observed on Pd / TiAl and Pd / CeAl catalysts, which is consistent with their light-off performance in the presence of moisture and SO2. At higher temperatures (500°C), the deactivation effect of moisture is reversed and dehydroxylation occurs, with Pd / ZrAl showing higher SO2 tolerance than Pd / Al2O3, probably because of its lower tendency to form bulk sulfate in the presence of moisture as observed by DRIFTS results. This suggests that the strong adsorption of moisture on Pd active sites in the presence of adsorbed sulfur species further accelerates the deactivation of the Pd catalyst.

[0124] Next, the applicant studied the regeneration of the catalyst under wet dilute reaction conditions by heating the catalyst and maintaining it at 600°C for 30 minutes ( Fig.12b R1 region: Fig.12 b is Fig.12 a Continuation at the 7th hour). Although both Pd / Al2O3 and Pd / ZrAl showed complete methane conversion at 600 °C (95% conversion for Pd / CeAl), no significant activity recovery was observed after the reaction temperature was cooled to 450 °C ( Fig.12 b Region M4). The original Pd / Al2O3, Pd / CeAl, and Pd / TiAl show further activity loss after high temperature treatment. This indicates that high temperature treatment of the SO2-poisoned catalysts under dry reaction conditions fully restores the activity of Pd / ZrAl and partially restores the activity of Pd / Al2O3 and Pd / TiAl ( Fig.11 ), while treatment under wet lean conditions may promote the overflow of SOx species from the carrier to the PdO site.

[0125] Subsequently, a second regeneration procedure was performed at 550 °C for 30 min at a wet reducing reaction mixture ( Fig.12 b R2 zone). After this regeneration step, the reactor is cooled back to 450°C ( Fig.12 b M5 region), the activities of Pd / Al2O3 and Pd / ZrAl both recovered to levels comparable to those before sulfur poisoning, although Pd / ZrAl exhibited higher activity. In contrast, the catalytic activities of Pd / TiAl and Pd / CeAl dropped drastically. To confirm these observations, the regenerated catalysts were subjected to light-off tests under wet conditions, and their performance was compared with that of the respective fresh catalysts under the same reaction conditions. Fig.13 a shows the methane light-off performance of the regenerated catalyst under wet lean reaction conditions, with fresh Pd / Al2O3 as reference. Figure 8 The comparison of each regenerated catalyst with the fresh catalyst is shown. The results confirm that the regenerated Pd / ZrAl fully recovered its catalytic activity, while Pd / Al2O3, Pd / CeAl, and Pd / TiAl only achieved partial activity recovery. These results indicate that wet reduction treatment is a promising regeneration strategy as it is able to fully restore the activity of Pd / ZrAl and significantly restore the activity of Pd / Al2O3 at a low regeneration temperature of 550°C.

[0126] Regeneration under a reducing CH4 atmosphere favors the reduction of sulfate by CH4 activated on metallic Pd sites. Regeneration under a reducing CH4 atmosphere is more efficient than H2 regeneration because Pd metal tends to sinter and / or form PdS under H2 atmosphere. Deactivation effects and only partial activity recovery were observed after regeneration both in the presence and absence of moisture. DRIFTS and TPD studies indicate that the lower regeneration rates of Pd / TiAl and Pd / CeAl are related to the stability of sulfate on these catalysts and the spillover of sulfur from the support to the Pd active sites. The spillover of residual sulfur can lead to re-poisoning of Pd and hinder the re-oxidation of Pd after reductive regeneration.

[0127] Based on these observations, the applicant concluded that, under dry and wet conditions, while ZrO2 has a positive effect on enhancing the sulfur resistance of Pd catalysts by inhibiting the formation of bulk sulfate and promoting the decomposition and desorption of sulfur species during catalyst regeneration, TiO2 and CeO2 exhibit a negative effect. To further determine the role of ZrO2 in enhancing catalyst sulfur resistance and regeneration, a series of poisoning and wet reduction regeneration cycles were performed on Pd / Al2O3 and Pd / ZrAl at 500°C ( Fig.13 b). Cyclic poisoning-regeneration experiments showed that while both catalysts could be effectively regenerated after four poisoning cycles, the sulfur tolerance of the original Pd / Al2O3 catalyst decreased faster with each poisoning step, indicating a gradual decrease in its ability to resist SO2, which may be due to the formation and accumulation of more stable bulk sulfates. This further proves that the ZrO2-modified catalyst is able to continuously and more effectively decompose sulfur species near the Pd active sites (even at a low regeneration temperature of 500°C), thereby successfully recovering its ability to catalyze methane oxidation.

[0128] Characterization and evaluation of regenerated catalysts

[0129] In situ CO DRIFTS analysis of the regenerated catalyst further revealed the interaction between the surface palladium and the residual sulfur and how different promoters affect this interaction compared to the fresh catalyst ( Fig.14 Similar to the fresh catalyst, CO was adsorbed on the corners and edges of Pd NPs (2080 cm-1), and the bridges were adsorbed on the step sites of Pd particles (1978 cm-1). -1 ), Pd (1945~1864cm -1 ) adsorption on bridge sites and vacancy sites. The adsorption of CO on Pd on the regenerated catalyst reflects the regenerability of the catalyst, which in turn is affected by the type of promoter, as mentioned above. Compared with the fresh sample, the regenerated Pd / CeAl( Fig.14 c) and Pd / TiAl( Fig.14d) The intensity of the CO adsorption band is significantly weakened. During the catalyst sulfurization process, due to the interaction between the Pd site and the sulfur species, the CO adsorption peak on the Pd site is significantly reduced, and in some cases disappears completely, resulting in the inability of the Pd site to adsorb CO.

[0130] Each regenerated catalyst has a Pd particle size of 2080 cm -1 ) have strong CO adsorption at the corners and edges, but the adsorption intensity on Pd / TiAl is weak. Fig.14 a) and Pd / ZrAl catalyst ( Fig.14 b), CO can be observed at the Pd stage (1978 cm -1 ). Note that Pd / ZrAl and Pd / Al2O3 show the highest activity recovery after regeneration ( Fig.11 a and b, 6b and 7a). These results demonstrate that: (i) the regenerated Pd sites are available for CO adsorption. (ii) the bridge and hollow sites of Pd interact more strongly with the residual sulfur on the catalyst. (iii) the step sites are associated with activity recovery because these sites become more prominent and dissolved in the regenerated Pd / Al2O3 and Pd / ZrAl after the hollow sites weaken, which is consistent with the previous demonstration of the activity of these sites for methane oxidation and the activity recovery after sulfidation.

[0131] The weakened CO adsorption on the regenerated Pd / TiAl and Pd / CeAl catalysts indicates that the Pd sites are unavailable for CO adsorption due to their interaction with the retained sulfur on the catalysts. Since the retained sulfur in the catalysts may affect the mobility of lattice oxygen and affect the redox performance of PdO for methane oxidation, we believe that the low regeneration of Pd / TiAl and Pd / CeAl (under the regeneration conditions studied) is caused by the stability of sulfur species and the spillover of sulfur from the support to the active sites. The availability of Pd sites for CO adsorption is significantly reduced in the CO-DRIFT spectra of the regenerated catalysts.

[0132] The above tests and examples demonstrate that the type of promoter and its chemical properties are key factors to consider when designing methane reduction catalysts under realistic conditions of SO2 and moisture. The results show that promoters and moisture affect the type, distribution and stability of sulfur on the catalyst, which in turn affects the activity and regeneration efficiency of the catalyst. Compared with the original Pd / Al2O3 catalyst, the TiO2 and CeO2 modified catalysts are more likely to form sulfate species than the ZrO2 modified alumina supported Pd catalyst. The sulfates formed around the Pd active sites on ZrO2 are mainly less stable surface sulfates. In contrast, more stable blocky sulfate species are formed on TiO2 and CeO2 modified catalysts, and the strength of these species is affected by high temperature and moisture.

[0133] Effective regeneration of poisoned catalysts is key to the practical application of methane oxidation catalysts. The stability of sulfate species on the catalyst affects the regeneration efficiency of the catalyst. Under dry reaction conditions, surface sulfates formed in the presence of ZrO2 are easily decomposed under reaction conditions, thereby fully restoring the activity of the poisoned catalyst, while CeO2 and TiO2 favor the formation of more stable sulfate species that are not easily decomposed and spill over to the Pd sites, making the recovery of catalytic activity more challenging. The results of regeneration studies showed that a rich, reducing methane atmosphere can fully regenerate the ZrO2-promoted catalyst, with significant sintering of Pd nanoparticles and significant recovery of Pd / Al2O3 activity. The results of cyclic poisoning and regeneration tests showed that while sulfur accumulation affects the regeneration efficiency of Pd / Al2O3, the presence of ZrO2 allows for continuous and effective decomposition of sulfur species, thereby effectively restoring activity after poisoning and regeneration cycles. On the other hand, the formation of stable sulfur species and spillover of sulfur on TiO2 and CeO2 inhibit the regeneration of Pd active sites. It is also worth noting that under the reaction conditions of the present application, the Pd active sites on the TiO2-promoted catalyst are prone to moisture-induced sintering through particle agglomeration and enlargement.

Claims

1. A methane oxidation catalyst with improved sulfur resistance and regeneration capability, characterized in that: The catalyst comprises a fully hydroxylated γ-Al2O3 carrier, a catalytically active component and a catalytic promoter, wherein the catalytically active component comprises the precious metal Pd, and the catalytic promoter comprises at least one of ZrO2, CeO2 or TiO2.

2. The methane oxidation catalyst with improved sulfur resistance and regeneration ability according to claim 1, characterized in that: The completely hydroxylated γ-Al2O3 carrier is obtained by subjecting the γ-Al2O3 carrier to complete hydroxylation treatment and then drying it at 90°C overnight.

3. The methane oxidation catalyst with improved sulfur resistance and regeneration ability according to claim 1, characterized in that: The content of the catalyst promoter is 4%-20% of the total mass of the methane oxidation catalyst.

4. The methane oxidation catalyst with improved sulfur resistance and regeneration capability according to claim 3, characterized in that: The content of the catalyst promoter is 4%, 8%, 12% or 20% of the total mass of the methane oxidation catalyst.

5. The methane oxidation catalyst with improved sulfur resistance and regeneration ability according to claim 1, characterized in that: The content of the noble metal Pd in ​​the catalytically active component, calculated as a single substance, accounts for 0.5-1.5% of the total mass of the methane oxidation catalyst.

6. A method for preparing a methane oxidation catalyst with improved sulfur resistance and regeneration ability according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of fully hydroxylated γ-Al2O3 support: γ-Al2O3 was added to ammonia water and dried at 85-95°C overnight to ensure that the alumina support was fully hydroxylated; (2) Preparation of catalyst promoter-Al2O3: Use a reflux condenser to place the fully hydroxylated alumina carrier obtained in step (1) into a reactor, and then add anhydrous ethanol to mix; add anhydrous ethanol to a centrifuge tube, and then titrate the catalyst promoter precursor solution into the centrifuge tube; pass cooling water into the condenser, set the temperature of the heating jacket to 75-85°C, and the speed to 350-450rpm; when the temperature in the reactor reaches 78-82°C, slowly drip the liquid in the centrifuge tube into the reactor, and after dripping, add anhydrous ethanol to the centrifuge tube for rinsing and then titrate; after reacting for 1.5-2.5 hours, remove the condenser to evaporate the ethanol, and the obtained dry powder is dried at room temperature overnight, and then calcined at 550-650°C for 3-5h, with a heating rate of 2-5°C / min, to obtain a composite oxide; (3) Preparation of supported metallic palladium: Tetraamine palladium (II) nitrate solution is diluted with ultrapure water by a wet impregnation method, and then added to the composite oxide, and then ultrapure water is dropped. The resulting mixture is stirred and then evaporated to dryness at 75-85°C. The resulting dry powder is calcined at 450-550°C at a temperature gradient of 2-5°C / min for 4-6 hours to obtain a methane oxidation catalyst.

7. The method for preparing a methane oxidation catalyst with improved sulfur resistance and regeneration ability according to claim 6, characterized in that: The bimetallic oxide described in step (3) is calcined at 600° C. for 4 h at a heating rate of 3° C. / min.

8. The method for preparing a methane oxidation catalyst with improved sulfur resistance and regeneration ability according to claim 6, characterized in that: The calcination in step (4) is carried out at 500° C. for 5 h at a temperature gradient of 3° C. / min.

9. An application of a methane oxidation catalyst for improving sulfur resistance and regeneration ability, characterized in that: It is used in the exhaust gas purification system of lean-burn natural gas engines.